Monopelopia Fittkau, 1962, a newly recorded genus from Oriental China (Diptera, Chironomidae) with a description of Monopelopia zhengi Lin sp. n. - Duan, Xin; Chang, Tong; Jiao, Ke-Long; Wang, Xin-Hua; Lin, Xiao-Long (Zootaxa, 2021)
The genus Monopelopia Fittkau, 1962 is newly recorded from Oriental China. Monopelopia zhengi Lin sp. n., is described and illustrated based on an adult male from Jianfengling National Nature Reserve, Hainan, China. In addition, an updated key to adult males of Monopelopia is provided.